"Boomeranging" and Delinquent Behavior in Emerging Adulthood: A Person-Centered Approach to Studying Role Change. (December 2017) - Hill, Jessica M.; Bosick, Stacey J.
Role change is a central feature of the transition to adulthood. These transitions are not always linear. It is unclear whether "boomeranging" back into dependent roles is problematic to later life outcomes or represents healthy role exploration. Using a person-centered approach, we explore whether role dependence (remaining in dependent roles), role progression (movement into independent roles), or role boomeranging (moving from independent to dependent roles) clusters within individuals, using a sample of Dutch emerging adults. Three distinct classes emerged. The "experimenter" class was characterized by low progression into independent roles. These participants experimented with employment, education, and relationships but experienced highest levels of boomeranging compared to other classes ("early independents" and "achievement-focused singles"). Experimenters were most likely to be involved in delinquency. We discuss the low levels of boomeranging found in our young sample and whether the experimenter's pattern of role change signals a pathway to continued instability into adulthood.